Pelaksanaan Hukum Adat dalam Pembangunan Infrastruktur Berkelanjutan - Mutiara Ramadhani; Diyah Ayu Riyanti (CV Rewang Rencang, 2022)
Infrastructure development in Indonesia is not easy to implement because of the diversity of cultures and geographical conditions, which made Indonesia seek infrastructure development following indigenous peoples. This research focuses on the legal basis for using indigenous peoples' land and the role and enforcement of customary law in sustainable infrastructure development. This type of writing study uses the juridical-normative method through primary and secondary legal study materials to find answers to the research. With this, a conclusion that draws infrastructure development that uses customary rights for the public interest can carry out by way of the handover of land by the authorities together with the owners of traditional rights based on an agreement between indigenous peoples and the applicable provisions.